The Influence of Leadership and Work Motivation on IAKN Tarutung Employee Performance - Rismawati Rajagukguk; Binur Panjaitan; Oktober Tua Aritonang (Formosa Journal of Science and Technology, 2023)
This research aims to determine whether there is an influence of Leadership and Work Motivation partially and together on Employee Performance, with the hypothesis that there is a positive and significant influence between Leadership and Work Motivation partially and together on Employee Performance. This research uses descriptive and inferential quantitative methods. The research population was all IAKN Tarutung employees, totaling 113 people with a sample of 43 people. The research instrument is a closed questionnaire, which was prepared by the researcher based on research variable indicators. The results of data analysis show: 1). Obtained a coefficient of determination of 45.15% and Fcount>Ftable, namely 33.22>4.08, meaning that there is a positive and significant influence between leadership on employee performance of 45.15%; 2). Obtained a coefficient of determination of 36.12% and Fcount>Ftable, namely 22.95>4.08, meaning that there is a positive and significant influence between work motivation on employee performance of 36.12%; 3). Obtained a multiple correlation coefficient of R = 0.729 and a multiple determination coefficient of 53.14%, meaning that there is a positive and significant influence between leadership and work motivation together on employee performance of 53.14%, thus Ho is rejected and Ha is accepted, so it can be concluded Leadership and work motivation influence the performance of IAKN Tarutung employees positively and significantly because they have been empirically tested. Top of Form